2013
DOI: 10.1007/s00467-013-2413-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of mesenchymal stem cell-derived microvesicles in tissue repair

Abstract: Results from recent studies suggest that the beneficial effect of stem cell-based therapy is mainly dependent on a paracrine effect. The paracrine hypothesis implicates the ability of stem cells to limit injury or coordinate repair through the release of soluble factors. Among these factors microvesicles (MVs) have emerged as a mechanism through which stem cells may reprogram injured cells. In fact, MVs released from stem cells may deliver proteins, bio-active lipids and nucleic acids to injured cells. In part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 51 publications
5
51
0
Order By: Relevance
“…Previous studies demonstrated that EVs produced by bone-marrow derived MSCs contribute to tissue remodeling after injury [12]. In the present study we focused on the angiogenic potential of EVs derived from ASCs that may represent a suitable source of adult stem cells for regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that EVs produced by bone-marrow derived MSCs contribute to tissue remodeling after injury [12]. In the present study we focused on the angiogenic potential of EVs derived from ASCs that may represent a suitable source of adult stem cells for regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%
“…ASC conditioned medium contains several growth factors including vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF) and may mimic the beneficial effects of cells [10,11]. We previously found that EVs released from stem/progenitor cells may, at least in part, account for the effect of conditioned medium [12]. EVs derived from endothelial progenitor cells were shown to activate an angiogenic program in quiescent endothelial cells [13].…”
Section: Introductionmentioning
confidence: 99%
“…Transfer of this biological material to adjacent or distant cells may facilitate communication between different cell types. Secreted EVs express molecules that reflect the cells of origin and, in the field of regenerative medicine, EVs derived from MSCs (MSC-EVs) have been shown to be able to mimic the therapeutic effects of the MSCs in kidney, cardiac, and brain injuries (29, 30). EVs released from MSCs could also be involved in the effects of MSCs on tumor growth and behavior.…”
Section: Introductionmentioning
confidence: 99%
“…These classical biomarkers have poor sensitivity and specificity for the detection of renal injury [16]. Moreover, the infusion of stem cells is replaced by a new approach that consists in administering vesicles obtained from cultured stem cells [17] or proteins/genetic material obtained from microvesicles [18].…”
Section: Expert Opinionmentioning
confidence: 99%